Incorporating Digital Technology in the General Education Classroom - Eddia Solas; Frances Sutton (Research in Social Sciences and Technology, 2018)
The implementation of technology-based pedagogic practices is becoming increasingly significant in higher education as the admission of digital natives increase. This generation of students, so defined as digital natives because they grew up using computers, tablets, smart phones and other digital technology, show a high level of technological competence, but exhibit deficiencies in competencies related to digital academic tools. A group of activities which supports learning, and facilitates student academic success, were compiled in a 28-item challenge for beginning General Education students, as a part of a Life and Study Skills course. Each challenge invited students to access some aspect of digital technology which has the potential to increase their academic competence. The main aim of the exercise was to increase students’ digital academic literacy, exposing them to applications and ICT skills which would increase their efficiency, self-efficacy and accuracy in executing academic tasks. The technology tools used were aimed at accomplishing tasks such as group formation and communication, notetaking, information capture, summarization, synchronous and asynchronous collaboration on tasks, referencing, formatting, grammar check, plagiarism and assessment. Students were challenged to complete particular tasks using specific applications. A screenshot of each completed activity was submitted as evidence of task completion. Students were given 28 days to complete the tasks, after which they were required to do two quizzes, using learning platforms they were exposed to in the challenge, demonstrating their new found proficiencies.